A grid-free particle tracking simulation for tracer dispersion in porous reservoir model. (September 2015) - Widiatmojo, Arif; Sasaki, Kyuro; Yousefi-Sahzabi, Amin; Nguele, Ronald; Sugai, Yuichi; Maeda, Atsushi
Highlights: We used particle tracking to simulate tracer dispersion in porous model. The method of images is used to generate velocity vectors within the flow domain. The visualization of dispersing particles is simple and straightforward. The effects of numerical parameters are evaluated. Results are in well agreement with the experimental and grid-based simulation. Abstract: Tracer test is a useful method to investigate various phenomena in geological porous media including groundwater contaminant transport, sweep efficiency and retention time in oil reservoir, reservoir characterization, fractures orientation assessment, as well as geothermal reservoir evaluation. Numerical methods are powerful tools in interpreting tracer test results. However, they are limited by computational restrictions which include finer grid requirements and small calculation steps. In this study, an analog model of a quarter five-spot porous reservoir was simulated by using random walk particle tracking method. This scheme used 'method of images' with pairs of injector–producer potential flow to generate the velocity vectors instead of conventionally solving Darcy's equation to obtain grid velocities. Simulated breakthrough concentration profiles and flow visualization were compared with both experimental results and Eulerian-grid based finite volume simulation. The predicted breakthrough curves of tracer concentration were found to agree with experimental data sets. In addition to be free from numerical errors as often encountered in grid-based simulation, the proposed particle tracking model showed a faster computational time. Unlike the conventional grid method, this technique provides inherently smooth and continuous flow field at arbitrary position within the reservoir model.